The possible mechanism and research progress of ACE2 involved in cardiovascular injury caused by COVID-19: a review - Luo, Dan; Bai, Mengzhe; Zhang, Wei; Wang, Junnan (Frontiers in Cardiovascular Medicine, 2024)
ACE2 is the earliest receptor discovered to mediate the entry of SARS-CoV-2. In addition to the receptor, it also participates in complex pathological and physiological processes, including regulating the RAS system, apelin, KKS system, and immune system. In addition to affecting the respiratory system, viral infections also interact with cardiovascular diseases. SARS-CoV-2 can directly invade the cardiovascular system through ACE2; Similarly, cardiovascular diseases such as hypertension and coronary heart disease can affect ACE2 levels and exacerbate the disease, and ACE2 dysregulation may also be a potential mechanism for long-term acute sequelae of COVID-19. Since the SARS CoV-2 epidemic, many large population studies have tried to clarify the current focus of debate, that is, whether we should give COVID-19 patients ACEI and ARB drug treatment, but there is still no conclusive conclusion. We also discussed potential disease treatment options for ACE2 at present. Finally, we discussed the researchers’ latest findings on ACE2 and their prospects for future research.